Low-Dimensional Carbon Allotropes: Ground- and Excited-State Charge Transfer with NIR-Absorbing Heptamethine Cyanine - Roth, Alexandra Marina; Schierl, Christoph; Ferrer-Ruiz, Andres; Minameyer, Martin; Rodriguez-Perez, Laura; Villegas, Carmen; Angeles Herranz, Ma; Martin, Nazario; Guldi, Dirk Michael (Chem, 2017)
At the focal point of our studies are mutual interactions between an anionic heptamethine cyanine and individualized single-walled carbon nanotubes (SWCNTs) or exfoliated nanographene (NG). Here, we report the distinct near-infrared absorption of the heptamethine cyanine, which assists in visualizing the electronic interactions in the ground state with ease and precision. In statistical Raman assays, we conclude from downshifted 2D- and G-modes for SWCNTs, as well as upshifted 2D- and downshifted G-modes for NG, that these electronic interactions result in stable n-doping of SWCNTs and NG. Key to this shift of charge density is the electron-donating character of the heptamethine cyanine. In the excited state, a complete but metastable transfer of charges is accompanied by a radical-ion-pair state that lives for several nanoseconds. Such a time domain has not yet been realized, for example, in NG to date.
CRIS-Team Scopus Importer:2022-04-14
Keywords: carbon nanotubes; cyanines; electron transfer; graphene; n-doping; NIR-light harvester; organic electronics; Raman spectroscopy; transient absorption spectroscopy